2020
DOI: 10.1177/2151459320971568
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Proximal Humerus Fractures in Geriatric Patients: A Review

Abstract: High-energy proximal humerus fractures in elderly patients can occur through a variety of mechanisms, with falls and MVCs being common mechanisms of injury in this age group. Even classically low-energy mechanisms can result in elevated ISS scores, which are associated with higher mortality in both falls and MVCs. These injuries result in proximal humerus fractures which are commonly communicated via Neer’s classification scheme. There are many treatment options in the armamentarium of the treating surgeon. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“… 9 Elderly female patients may have underlying bone density deficits before sustaining a fragility fracture that may be undiagnosed before injury. 27 , 48 With the gaining popularity of RSA for the treatment of the aging population and increasing prevalence of proximal humeral fragility fractures, this study aimed to evaluate how gender and age have affected definitive treatment selection over the last decade.…”
mentioning
confidence: 99%
“… 9 Elderly female patients may have underlying bone density deficits before sustaining a fragility fracture that may be undiagnosed before injury. 27 , 48 With the gaining popularity of RSA for the treatment of the aging population and increasing prevalence of proximal humeral fragility fractures, this study aimed to evaluate how gender and age have affected definitive treatment selection over the last decade.…”
mentioning
confidence: 99%
“…The meta-analysis of Walters et al. [ 23 ] concluded that the surgical choice should consider the age of the patient, the level of independence, the bone quality, the comorbidities, and the fracture pattern. Healthy patients with complex pattern fractures are candidates for surgical synthesis with plate and screws; HA should be reserved for patients with poor bone quality and pattern fractures that might lead to AVN (high risk of cutout screws); RSA should be considered for elderly patients, maybe after a first attempt with ORIF or HA [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement in fixation techniques, a large collection of poor outcomes and surgical complications are still prevalent, particularly in the presence of osteoporosis. 3,4 Many factors have been demonstrated to be responsible for the poor outcome of PHFs, including low local bone mineral density, medial calcar comminution, length of metaphyseal segment, and coronal displacement of the fracture at the onset. [3][4][5][6][7] Gardner et al 8 have underlined mechanical support of the medial column was essential to maintain fracture reduction.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many factors have been demonstrated to be responsible for the poor outcome of PHFs, including low local bone mineral density, medial calcar comminution, length of metaphyseal segment, and coronal displacement of the fracture at the onset. [3][4][5][6][7] Gardner et al 8 have underlined mechanical support of the medial column was essential to maintain fracture reduction. They concluded that accurate reduction of the medial cortex created a load sharing condition and minimized the forces at the screwbone interface.…”
Section: Introductionmentioning
confidence: 99%